Dedicated Chalazion Clinic as a Tool for Early Surgical Education in Ophthalmology Residency - Lin, Lisa Y.; Armstrong, Grayson W.; Gardiner, Matthew; Lorch, Alice; Freitag, Suzanne K.; Yadav, Prashant (Journal of Academic Ophthalmology, 2023)
Objective Ophthalmology residency programs aim to improve resident surgical teaching through increased surgical exposure over a 4-year period. Resident-centric surgical clinics across various surgical specialties have been established to help develop surgical autonomy and experience. We present the first demonstration of a resident-centric chalazion incision and drainage clinic (chalazion clinic) in an ophthalmology residency with the goal of increasing early surgical exposure to residents.Design The chalazion clinic was founded in July 2019. It is a once weekly procedure clinic conducted by an ophthalmology resident and supervised by an ophthalmology attending. Patients with chalazia were referred directly to this clinic for evaluation and management, rather than the oculoplastics clinic as they were in the past. Retrospective review of Accreditation Council for Graduate Medical Education (ACGME) case logs of all residents per academic year before and after establishment of the chalazion clinic was performed in order to assess the impact on residents' chalazion procedures numbers per academic year.Setting The study involved a single academic ophthalmology department.Participants Ophthalmology residents of all years were present.Results A resident of any year performed an average of 3.0 chalazion procedures per year in the 2018 to 2019 academic year, 3.8 in 2019 to 2020, and 8.4 in the 2020 to 2021, which represents a 180% increase in procedure numbers per resident. Among post-graduate-year 2s (PGY)2s, the average number of chalazion procedures increased from 2.1 procedure per year to 22.3 per year (961.9% increase).Conclusion To the best of our knowledge, this is the first description of a dedicated resident-centric chalazion clinic in an ophthalmology residency program. PGY2s demonstrated the largest increase in procedural numbers. While chalazion incision and drainage is a minor procedure, increased exposure to surgical procedures early in training could help improve residents' skills and confidence. This clinic provides a proof of concept of a dedicated minor procedure clinic for ophthalmology residents to increase early procedural volume.
Keywords: ophthalmology; chalazion; surgical education; residency